International Law Review Of Space Debris Mitigation Efforts - Ed. Siregar, El Renova; Paramita Prabandari, Adya; Siregar, Naek (CV. Inara, 2024)
Space debris has become an increasingly pressing issue in space exploration and utilization. This article conducts a comprehensive review of aspects of international law relating to space debris mitigation efforts. This research analyzes existing legal frameworks, including relevant multilateral treaties and international legal principles related to the space environment. With a focus on the principles of shared responsibility and avoidance of damage to the space environment, the study identifies key challenges in managing space junk and reducing the risk of collisions in earth orbit. An in-depth analysis of the role of national space agencies and international organizations in implementing mitigation measures was also carried out. In the context of international cooperation, this article evaluates existing collaborative efforts and proposes new measures to improve the effectiveness of space debris mitigation. A better understanding of legal responsibility and burden-sharing in addressing these issues became a central point in the study. By analyzing recent developments in space law and international environmental regulations, this article provides insight into the direction the global community might take in addressing future space debris mitigation challenges. It is hoped that this research can provide guidance for policymakers, academics, and legal practitioners in their efforts to maintain a clean and sustainable space environment.